Multiboronic acid-conjugated chitosan scaffolds with glucose selectivity to insulin release - Siddiqui, Nabil A.; Billa, Nashiru; Roberts, Clive J. (Taylor & Francis, 2017)
The principal challenge for the use of boronic acids (BA) as glucose sensors is their lack of specificity for glucose. We examined the selectivity of and insulin release from two boronic acids- (2-formyl-3-thienylboronic acid (FTBA) and 4-formylphenylboronic acid (FPBA)) conjugated chitosan scaffolds to glucose and fructose. Adsorption of glucose to BA: chitosan conjugates was dose-dependent up to 1:1 at 35 and 42% for FPBA and FTBA respectively but the FTBA conjugates adsorbed more glucose and fructose at respective FPBA ratios. The affinity of both BA conjugates to glucose decreased with increase in BA ratio. On the other hand, the affinity of both BA conjugates for fructose decreased from ratio 1:1 to 2:1 then rose again at 3:1. Insulin release from FPBA nanoparticles (FPBAINP) and FTBA nanoparticles (FTBAINP) were both concentration-dependent within glyceamically relevant values (1–3 mg/ml glucose and 0.002 mg/ml fructose). Furthermore, the total amounts of insulin released from FPBAINP in both the media were higher than from FTBAINP. Both FPBAINP and FTBAINP have the potential for development as a glucose-selective insulin delivery system in physiological settings.